Unleashing Village Potential: Empowering Farmers Towards Food Independence - Al Banda Arya Rekso Negoro (CV. Sutan Mandiri Sejahtera, 2026)
Village dependence on food supplies from outside the region remains high due to the suboptimal utilization of local potential and weak farmer capacity. Objective: This study aims to analyze the potential of the village agricultural sector and formulate farmer empowerment strategies to achieve sustainable food independence. Method: This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and Focus Group Discussions (FGDs) with farmer groups and the village government. Field findings indicate that Cibeusi Village possesses strategic assets in the form of fertile land, a tradition of mutual cooperation (rereongan), and superior commodities (organic rice and palm sap). However, this potential is hampered by the aging farmer population and the debt-based system of middlemen. The empowerment strategy, using the Asset-Based Community Development (ABCD) approach, successfully integrated the strengthening of bio-agronomic capacity, revitalizing the role of Gapoktan (Farmer Groups) as supply chain partners, and creating added value (agro-processing) such as palm sugar through digital marketing. This synergy constructs a closed-loop system model that successfully transforms farmers from price takers to price makers. Endogenous asset-based farmer empowerment is key to breaking structural marginalization and building a stronghold of independent food security within rural units